2011
DOI: 10.18785/jetde.0401.10
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Reality: An Overview and Five Directions for AR in Education

Abstract: Augmented Reality (AR) is an emerging form of experience in which the Real World (RW) is enhanced by computer-generated content tied to specific locations and/or activities. Over the last several years, AR applications have become portable and widely available on mobile devices. AR is becoming visible in our audio-visual media (e.g., news, entertainment, sports) and is beginning to enter other aspects of our lives (e.g., e-commerce, travel, marketing) in tangible and exciting ways. Facilitating ubiquitous lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
362
1
27

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 643 publications
(453 citation statements)
references
References 30 publications
8
362
1
27
Order By: Relevance
“…The simulated object can be in 2D and 3D forms, e.g. a sound file, video, or text information, and the user can perceive the additional content in a real-world environment [11]. As technological advancement has rendered AR more efficient and ARcompatible devices, such as PCs and mobile phones have become small and compact, AR tends to be used more frequently in teaching [12].…”
Section: Introductionmentioning
confidence: 99%
“…The simulated object can be in 2D and 3D forms, e.g. a sound file, video, or text information, and the user can perceive the additional content in a real-world environment [11]. As technological advancement has rendered AR more efficient and ARcompatible devices, such as PCs and mobile phones have become small and compact, AR tends to be used more frequently in teaching [12].…”
Section: Introductionmentioning
confidence: 99%
“…Ayrıca yorumlama, problem çözme (Schrier, 2006) ve yaratıcı düşünme becerisini artırmakta (Ivanova ve Ivanov, 2011), öğrencilere esnek bir öğrenme ortamı sunmaktadır. Dahası eğitime uygun bir şekilde entegre edildiğinde otantik öğrenme, durumsal öğrenme ve yapılandırmacı öğrenme gibi öğrenme yaklaşımlarını da destekleyebilmektedir (Johnson, Smith, Willis, Levine ve Haywood, 2011;Kirner, Reis ve Kirner, 2012;Wojciechowski ve Cellary, 2013;Yuen, Yaoyuneyong ve Johnson, 2011).…”
unclassified
“…Results from those studies indicate that Bursztyn et al | Assessment of student learning using augmented reality field trips for mobile smart devices GEOSPHERE | Volume 13 | Number 2 students enjoy using the VFTs, and researchers see gains in interest in the material through the interactivity and immersive experience as compared to traditional learning (Spicer and Stratford, 2001;Stumpf et al, 2008;Jacobson et al, 2009;Pringle, 2013;Friess et al, 2016). AR usage in medical, engineering, and mathematics education has resulted in similar findings (e.g., Liarokapis et al, 2004;Yuen et al, 2011;Lee, 2012). Recent research has also investigated the use of mobile devices, such as smartphones, to further contextualize learning (Roschelle, 2003;McGreen and Sánchez, 2005;Clough et al, 2008).…”
Section: Introductionmentioning
confidence: 87%
“…Although on one hand, mobile AR technologies can represent a communication gap between incoming freshmen and educators (National Higher Education ICT Initiative, 2007;Perlmutter, 2011;Dahlstrom and Bichsel, 2014), studies have shown that simulations, games, and virtual field trips (VFTs) actually increase students' motivation (McGreen and Sánchez, 2005;Bell et al, 2009;Honey and Hilton, 2011;Johnson and Johnston, 2013;Bursztyn et al, 2017). There have been increasing reports of VFTs being used in a variety of college courses, including biology, medicine, engineering, geography, and geology (e.g., Spicer and Stratford, 2001;Liarokapis et al, 2004;Stumpf et al, 2008;Jacobson et al, 2009;Yuen et al, 2011;Lee, 2012;Pringle, 2013;Friess et al, 2016). Results from those studies indicate that Bursztyn et al | Assessment of student learning using augmented reality field trips for mobile smart devices GEOSPHERE | Volume 13 | Number 2 students enjoy using the VFTs, and researchers see gains in interest in the material through the interactivity and immersive experience as compared to traditional learning (Spicer and Stratford, 2001;Stumpf et al, 2008;Jacobson et al, 2009;Pringle, 2013;Friess et al, 2016).…”
Section: Introductionmentioning
confidence: 99%